Improving Emergency Preparedness and Safety Management in Physical Education Settings - Adi S; Cahyo Yuwono; Tri Nurharsono; Amelia Fitra Khasanah; Natalia Desy Putriningtyas; Sri Indah Ihsani; Made Bang Redy Utama; Hilmy Aliriad (Universitas Negeri Semarang, 2025)
The high risk of accidents in elementary school environments requires physical education teachers to have emergency response competencies, including the ability to perform first aid and cardiopulmonary resuscitation (CPR). However, most teachers have not received adequate training in this area. This community service activity aims to enhance the capacity of PE teachers through theoretical and practical training covering CPR, AED use, and the integration of safety protocols into physical education activities. The implementation method includes initial coordination with the school, a pretest, classroom and field training, demonstrations, a posttest, and evaluation using a Google Form-based questionnaire. The results of the activity showed a significant improvement in participants' competencies: 90% of teachers were more skilled in handling emergencies, 95% were able to integrate safety protocols into learning, and 100% obtained formal competencies in CPR skills. Additionally, 95% of teachers demonstrated improved support for the school's medical team system, and 90% were able to incorporate physical safety into the curriculum. These findings confirm the effectiveness of systematic and practical training in enhancing teachers' preparedness. In conclusion, strengthening teachers' competencies in school safety should be an integral part of education policy, and such training should be conducted regularly to ensure comprehensive student safety.